2019
DOI: 10.4168/aair.2019.11.4.548
|View full text |Cite
|
Sign up to set email alerts
|

Combination Effect of Titrated Extract ofCentella asiaticaand Astaxanthin in a Mouse Model of Phthalic Anhydride-Induced Atopic Dermatitis

Abstract: Purpose In our previous study, we demonstrated that both titrated extract of Centella asiatica (TECA) and astaxanthin (AST) have anti-inflammatory effects in a 5% phthalic anhydride (PA) mouse model of atopic dermatitis (AD). The increasing prevalence of AD demands new therapeutic approaches for treating the disease. We investigated the therapeutic efficacy of the ointment form of TECA, AST and a TECA + AST combination in a mouse model of AD to see whether a combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…Topical treatment with C. asiatica phytosome inhibited the expression of iNOS and COX-2, the activity of NF- κ B, and the release of TNF- α , IL-1 β , and IgE, leading to the suppression of inflammatory cell infiltration [ 41 ]. Furthermore, TECA mixed with astaxanthin augmented the inhibitory effect of TECA on PA-induced morphological changes in skin and ear thickness [ 42 ]. Interestingly, both topical and oral administration of C. asiatica ethanol extract decreased mast cell infiltration in the ear tissue and reduced the expression of various proinflammatory cytokines such as TNF- α , IL-4, IL-5, IL-6, IL-10, and IL-17 [ 43 ].…”
Section: Pharmacological Effects Of Centella Asiatica On Skin Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical treatment with C. asiatica phytosome inhibited the expression of iNOS and COX-2, the activity of NF- κ B, and the release of TNF- α , IL-1 β , and IgE, leading to the suppression of inflammatory cell infiltration [ 41 ]. Furthermore, TECA mixed with astaxanthin augmented the inhibitory effect of TECA on PA-induced morphological changes in skin and ear thickness [ 42 ]. Interestingly, both topical and oral administration of C. asiatica ethanol extract decreased mast cell infiltration in the ear tissue and reduced the expression of various proinflammatory cytokines such as TNF- α , IL-4, IL-5, IL-6, IL-10, and IL-17 [ 43 ].…”
Section: Pharmacological Effects Of Centella Asiatica On Skin Diseasesmentioning
confidence: 99%
“…Titrated extract of C. asiatica (TECA) treatment suppressed NF- κ B activity and subsequently inhibited the expression of TNF- α , IL-1 β , and IL-6 in a phthalic anhydride (PA)-induced atopic dermatitis (AD) animal model [ 40 ]. Furthermore, the addition of astaxanthin to TECA augmented the NF- κ B-mediated anti-inflammatory activity of TECA [ 42 ]. Another similar report supports the therapeutic effect of C. asiatica on AD via NF- κ B signaling.…”
Section: Underlying Mechanisms For the Pharmacological Effects Of Centella Asiatica On Skin Diseasesmentioning
confidence: 99%
“…As regards skin diseases, it has been reported that this carotenoid administered topically on the ear or back skin of mice alleviated hyperkeratosis and inflammatory response in a model of phthalic anhydride-induced atopic dermatitis. These actions were related to a down-regulation of NF-κB and its proinflammatory target genes iNOS and COX-2 [260,261]. In the same model, ATX-loaded liposomes were more effective than free ATX in alleviating skin inflammation due to inhibition of oxidative stress and STAT3 and NF-κB signaling pathways as well as a reduction of IgE, a marker of allergic inflammation [262].…”
Section: In Vivo Studiesmentioning
confidence: 98%
“…Hasilnya terdapat perbaikan klinis signifikan (morfologi dan ketebalan kulit di belakang telinga tikus) setelah aplikasi topikal TECA + AST dibandingkan TECA atau AST tunggal. 22 Pada pemeriksaan imunohistokimia didapatkan penurunan signifikan produksi NO setelah aplikasi topikal TECA + AST dibandingkan TECA atau AST tunggal. 22 Beberapa hasil penelitian dan systematic review pemberian antioksidan sistemik dan topikal pada kasus DA dalam rentang 10 tahun terakhir dirangkum dalam Tabel (Lampiran).…”
Section: Continuing Medical Educationunclassified